Zero-waste : reconsidering waste management for the future - Zaman, Atiq; Ahsan, Tahmina (2020)
"This book analyses 'zero-waste' as an emerging waste management strategy for the future, which considers waste prevention through innovative design and sustainable consumption practices. Drawing on a diverse range of case studies from Australia, Bangladesh, Japan, New Zealand, Sweden and the USA, this book explores why urban waste management systems still remain a major challenge for almost all cities around the world. Rejecting waste as an 'end-of-life' problem, Atiq Zaman and Tahmina Ahsan instead consider waste prevention through the zero-waste model, in which resources are utilized and consumed with minimum environmental degradation. In addition, the authors give extended discussion on why embracing the zero-waste concept will be beneficial for the circular economy. Providing a strategic zero-waste framework and an evaluation tool to measure waste management performance aimed towards zero-waste goals, this book will be of great relevance to students, scholars and policymakers with an interest in waste management, sustainable consumption, urban planning and sustainable development"--
Includes bibliographical references.
Keywords: Source reduction (Waste management); Refuse and refuse disposal; Sustainable living; Waste minimization -- Case studies; Recycling (Waste, etc.) -- Case studies